Accounts Payable, Intellectual Capital, and Corporate Value: Case Study of Food and Beverage Sector on IDX 2016-2020 - Wilujeng, Sri; Widodo, Heri (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study investigates the influence of account payable policy and intellectual capital on the value of companies within the food and beverages sub-sector listed on the Indonesia Stock Exchange. Purposive sampling was employed to select a sample of eight manufacturing companies for the period 2016-2020. Data were collected using documentation techniques and analyzed using SPSS. Results indicate that while the account payable policy significantly affects firm value, intellectual capital does not exhibit a significant impact. These findings shed light on the strategic importance of managing account payables for enhancing firm value in the food and beverages industry. Highlights : The study investigates the influence of account payable policy and intellectual capital on firm value in the food and beverages sector. Purposive sampling was used to select a sample of eight manufacturing companies listed on the Indonesia Stock Exchange. Findings reveal that while account payable policy significantly affects firm value, intellectual capital does not demonstrate a significant impact. Keywords: Account Payable Policy, Intellectual Capital, Firm Value, Food and Beverages, Indonesia Stock Exchange